PENERAPAN UNDANG-UNDANG NOMOR 7 TAHUN 2017 TENTANG SISTEM PEMILU PROPORSIONAL TERBUKA TERBATAS PADA PEMILU LEGISLATIF 2019 DI KOTA SALATIGA - Firdausy, Kharisma Aulia; Riwanto, Agus (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2019)
Legal Writing on the Application of Law No. 7 of 2017 concerning the Limited Open Proportional Election System for Voters’ Behavior in Facing the 2019 Legislative Elections in Salatiga City aims to explore the application of a limited open proportional electoral systemthe Election City in Salatiga in 2019. This research uses the type of empirical / socio-legal research that combines legal norms with sociological aspects by using the approach of legal principles and political behavior. The results showed that the regulation of a limited open proportional electoral system was contrary to the sovereignty of the people and the justice of the people and also the level of participation and voter behavior in the City of Salatiga had increased but was inversely proportional to the understanding of the use of a limited open electoral system. The renewal model for regulating the electoral system to create sovereign elections is to re-use another pure open election system.